High voltage vacuum insulation basic concepts and technological practice - Latham, R. V.
The past decade has witnessed dramatic growth in the diversity and complexity of device applications where vacuum is required to support either high voltages or high electric fields. This is particularly true in thespace industry, specifically for the development of space-based pulse power systems. This book presents an overview of the technological advances that have occurred since the publication of the Editors earlier book High Voltage Vacuum Insulation: The Physical Basis . In this latest book, contributions from internationally recognized professionals and researchers in the field provide.